The Implementation Of The Village Government's Internal Control System Through Independent Learning Programs: Integrated Independent Campuses - Meliana Puspitasari; Ihsan Nasihin (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
This study aims to propose a scheme for implementing an internal control system in the Village Government with the concept of an independent campus. The research method used is qualitative research with a literature review approach. The data used in this study are primary data and secondary data, with data collection techniques using literature and documentation. The data analysis technique used is qualitative data analysis by carrying out three stages of data analysis, namely data reduction, data display and conclusion and verifying. The results of the study illustrate that the implementation of the Village Government Internal Control System through the policy of independent learning: an Integrated independent campus and encourages the Contribution of the Role of Higher Education through a continuous Research Scheme. The integration model that uses several steps, namely literary research, campus collaboration with stakeholders, pilot projects to achieve the objectives of effective village government operations, produce reliable reporting (reliable bias), safeguard village assets, comply with statutory regulations and become input for drafting regulations. area of ​​the Village Government's internal control system